Solid hydrogen storage material, preparation method and application
Synthesis of MOFs material MIL-101 by microwave method solves the shortcomings in hydrogen storage efficiency and reaction time of traditional hydrothermal method, significantly improves the specific surface area of micropores and hydrogen adsorption amount, and achieves more efficient hydrogen storage performance, which helps for the development of renewable energy and environmental protection.
Patent Information
- Application Number
- CN202411527047.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-10
AI Technical Summary
The existing solid hydrogen storage materials have shortcomings in hydrogen storage efficiency and micropore specific surface area, especially in terms of hydrogen adsorption and reaction time. The traditional hydrothermal method consumes time and consumes a large amount of solvents, which affects the efficient storage of materials. Hydrogen performance.
The metal organic framework compound (MOFs) material MIL-101 is synthesized by microwave method, using chromium nitrate nitrate and terephthalic acid as raw materials, and the specific surface area of the material of the micropore through microwave hydrothermal reaction is increased, the reaction time is shortened and the hydrogen adsorption amount is increased. .
It significantly improves the micropore specific surface area and hydrogen adsorption amount of MOFs materials, shortens the synthesis time, reduces energy consumption, and improves hydrogen storage performance, helps reduce greenhouse gas emissions and promotes the utilization of renewable energy.
Smart Images

Figure CN119284834A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of chemical materials, and in particular relates to a solid hydrogen storage material, a preparation method and an application thereof. Background Art
[0002] Seeking clean energy technology for power generation with new energy is the current research focus. Hydrogen energy is a renewable energy source, and because of its wide source, high energy density, safety and controllability, and the characteristics of being storable and transportable, it has become a hot topic of research at home and abroad. Under standard conditions, hydrogen energy is insoluble in water, and hydrogen bonds are relatively stable, but it is flammable, easy to explode, highly diffusible, colorless and odorless, and it is not easy to be discovered after leakage. Therefore, the storage and transportation of hydrogen energy are crucial to the application of hydrogen energy. The storage method and the materials used for storage are two main concerns. Adsorption hydrogen storage is a physical hydrogen storage method that has emerged in recent years using adsorption theory. Materials with high specific surface area are the best materials for physical adsorption. The Chinese name of MOFs is metal organic framework compounds. MOFs is a new type of porous material that has developed rapidly in the past decade and has become a research focus in the field of international hydrogen storage. MOFs are skeleton materials with a periodic spatial network structure formed by self-assembly of multidentate ligands and metal ions or metal ion clusters. They are highly crystalline, have high porosity and specific surface area, and have rich and colorful structures and surface physicochemical properties. The structure and function of the MOFs framework and pore surface can be changed and improved through chemical modification. By adjusting the lattice dimension and pore size of MOFs materials, their chemical and physical properties can be precisely controlled; currently, the methods for synthesizing MOFs include: water / solvothermal method, diffusion method, mechanochemical method, electrochemical method and microwave method; water / solvothermal method is simple to operate and has low cost, but the experimental time is long, and a large amount of solvent is consumed to produce waste liquid; the reaction conditions of the diffusion method are mild, but it takes a long time; the mechanochemical method is a green synthesis method without solvent (or a small amount of solvent), with mild reaction conditions and short reaction time, which is suitable for large-scale synthesis; the electrochemical method has mild preparation conditions and can be carried out at room temperature, which is more energy-saving, and the crystal growth rate is fast, which is convenient for continuous production; the microwave method can greatly shorten the reaction time compared with the traditional solvent thermal method, because microwaves can accelerate the intermolecular movement so that the crystal can quickly nucleate and grow, accelerate the preparation efficiency of the material, and can effectively adjust the crystal size by changing the reaction temperature and time, solvent ratio, etc. The present invention introduces a simple method to increase the specific surface area of MOFs micropores to achieve enhanced hydrogen storage. Summary of the invention
[0003] The purpose of the present invention is to provide a solid hydrogen storage material, preparation method and application, using chromium nitrate Cr(NO3)2·9H2O nonahydrate as the metal center, terephthalic acid H2BDC as the organic ligand, deionized water as the solvent, and synthesizing MOFs material by microwave method, with short reaction time and simple synthesis process. The sample obtained in the experiment was synthesized by traditional hydrothermal method, and the results showed that: under the same conditions, the micropore specific surface area of MOFs synthesized by microwave method was significantly higher than that of MOFs synthesized by traditional hydrothermal method, and more importantly, the hydrogen adsorption amount of MOFs synthesized by microwave method was much larger. It shows that the micropore specific surface area of MOFs material can be increased by microwave method, thereby increasing the hydrogen storage capacity of the material. The benefit of the present invention to increase the micropore specific surface area of MOFs by microwave method to achieve enhanced hydrogen storage environment is significant, which helps to reduce greenhouse gas emissions, promote the use of renewable energy, improve air quality, and promote the sustainable development of society.
[0004] The technical solution adopted by the present invention is as follows:
[0005] A solid hydrogen storage material, the solid hydrogen storage material MIL-101 has a multi-level pore structure, and the specific surface area of the material is ≥3049m 2 ·g -1 The micropore volume is 1.42-1.70cm 3 ·g -1 , at a temperature of 77K and a pressure of 50 bar, the solid-state hydrogen storage material MIL-101≥4.365wt%.
[0006] A method for preparing a solid hydrogen storage material, the preparation method comprising the following steps:
[0007] Step 1: weigh 20-30 parts by mass of chromium nitrate nonahydrate and 8-12 parts by mass of terephthalic acid using an electronic balance, place them in a container, add 25-35 parts by mass of deionized water and a certain amount (with chromium nitrate as 1 molar equivalent) of hydrofluoric acid to obtain a mixed solution A;
[0008] Step 2: After ultrasonically mixing solution A for 30 minutes, transfer it to a microwave reactor lined with polytetrafluoroethylene, seal the microwave reactor and place it in a microwave hydrothermal reactor for reaction;
[0009] Step 3: Set the microwave power to 600 W, the temperature to 200-240 ° C, and the reaction time to 0.5-1.5 h;
[0010] Step 4: After the reaction is completed, the mixture is naturally cooled to room temperature, the reaction product is poured into a centrifuge tube and placed in a centrifuge, and the crude product is collected by centrifugation at a speed of 4000 r / min;
[0011] Step 5: Add 20-30 parts by mass of N,N-dimethylformamide DMF to the crude product, put it into a magnetic heating stirrer for activation, set the temperature to 70°C, the speed to 500r / min, and the activation time to 3h;
[0012] Step 6: After activation, the reaction product is placed in a centrifuge and centrifuged at 4000 r / min to collect the crude product;
[0013] Step 7: Add 15-25 parts by mass of anhydrous ethanol to the crude product, place it in a magnetic heating stirrer for activation, set the temperature to 60°C, the speed to 500r / min, and the activation time to 3h;
[0014] Step 8: After activation, the reaction product is placed in a centrifuge and centrifuged at 4000 r / min to collect the product; the product is then transferred to a beaker, placed in an oven, and dried at 80°C for 12 hours to obtain a dry solid-state hydrogen storage material MIL-101 sample.
[0015] Preferably, in step 2, the synthesis instrument is a microwave reactor.
[0016] Preferably, in step 3, the power of the microwave heating is 600 W, the temperature of the microwave heating is 200-240° C., and the time of the microwave heating is 0.5-1.5 h.
[0017] Application of a solid hydrogen storage material MIL-101 in the field of hydrogen storage.
[0018] The technical effects achieved by the present invention are:
[0019] The method uses chromium nitrate Cr(NO3)2·9H2O nonahydrate as the metal center, terephthalic acid H2BDC as the organic ligand, and deionized water as the solvent, and uses microwave method to synthesize the solid hydrogen storage material MIL-101. The reaction time is short and the synthesis process is simple. The sample obtained in the experiment is synthesized by the traditional hydrothermal method. The results show that under the same conditions, the micropore specific surface area of the solid hydrogen storage material MIL-101 synthesized by the microwave method is significantly higher than the micropore specific surface area of the solid hydrogen storage material MIL-101 synthesized by the traditional hydrothermal method. More importantly, the hydrogen adsorption amount of the solid hydrogen storage material MIL-101 synthesized by the microwave method is also much larger. It shows that the use of microwave method can increase the micropore specific surface area of the solid hydrogen storage material MIL-101, thereby increasing the hydrogen storage capacity of the material. The present invention uses microwave method to increase the micropore specific surface area of the solid hydrogen storage material MIL-101 to achieve the benefit of strengthening the hydrogen storage environment. It helps to reduce greenhouse gas emissions, promote the use of renewable energy, improve air quality, and promote the sustainable development of society. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is the XRD diagram of the solid hydrogen storage material synthesized by microwave method and traditional hydrothermal method in the present invention;
[0021] Figure 2 It is a pore size distribution diagram of the solid hydrogen storage material synthesized by microwave method and traditional hydrothermal method in the present invention;
[0022] Figure 3 It is a test diagram of hydrogen storage performance of solid hydrogen storage materials synthesized by microwave method and traditional hydrothermal method in the present invention. DETAILED DESCRIPTION
[0023] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is specifically described below in conjunction with embodiments. It should be understood that the following text is only used to describe one or several specific embodiments of the present invention, and does not strictly limit the scope of protection of the specific claims of the present invention.
[0024] Embodiment 1
[0025] A solid hydrogen storage material, the solid hydrogen storage material MIL-101 has a multi-level pore structure, and the specific surface area of the material is ≥3049m 2 ·g -1 The micropore volume is 1.42-1.70cm 3 ·g -1 , at a temperature of 77K and a pressure of 50 bar, the solid-state hydrogen storage material MIL-101≥4.365wt%.
[0026] Embodiment 2
[0027] A method for preparing a solid hydrogen storage material, the preparation method comprising the following steps:
[0028] Step 1: Use an electronic balance to weigh 2.4 g of chromium nitrate nonahydrate and 0.996 g of terephthalic acid, place them in a 100 mL beaker, add 30 mL of deionized water and 0.25 mL of hydrofluoric acid to obtain a mixed solution A;
[0029] Step 2: After ultrasonically mixing solution A for 30 minutes, transfer it to a microwave reactor lined with polytetrafluoroethylene, seal the microwave reactor and place it in a microwave hydrothermal reactor for reaction.
[0030] Step 3: Set the microwave power to 600 W, the temperature to 200 °C, and the reaction time to 1.0 h;
[0031] Step 4: After the reaction is completed, the mixture is naturally cooled to room temperature, the reaction product is poured into a centrifuge tube and placed in a centrifuge, and the crude product is collected by centrifugation at a speed of 4000 r / min;
[0032] Step 5: Add 25 mL of DMF to the crude product and place it in a magnetic heating stirrer for activation. Set the temperature to 70 ° C, the speed to 500 r / min, and the activation time to 3 h;
[0033] Step 6: After activation, the reaction product is placed in a centrifuge and centrifuged at 4000 r / min to collect the crude product;
[0034] Step 7: Add 25 mL of anhydrous ethanol to the crude product and place it in a magnetic heating stirrer for activation. Set the temperature to 60°C, the speed to 500 r / min, and the activation time to 3 h;
[0035] Step 8: After activation, the reaction product is placed in a centrifuge and centrifuged at 4000 r / min to collect the product. The product is then transferred to a beaker, placed in an oven, and dried at 80°C for 12 hours to obtain a dry solid hydrogen storage material MIL-101 sample.
[0036] It should be noted that the English abbreviation of the solid-state hydrogen storage material synthesized by this method is MIL-101, and the essence of the solid-state hydrogen storage material MIL-101 is a metal organic framework material. The English abbreviation of the metal organic framework compound material is MOFs material. In summary, the solid-state hydrogen storage material MIL-101 is one of the metal organic framework compounds MOFs.
[0037] Embodiment three:
[0038] The difference from Example 2 is that the reaction temperature in step 3 is 210° C. and the reaction time is 0.5 h.
[0039] Embodiment 4:
[0040] The difference from Example 2 is that in step 1, hydrofluoric acid is not added, the reaction temperature in step 3 is 210° C., and the reaction time is 0.5 h.
[0041] Embodiment five:
[0042] The difference from Example 2 is that in step 1, the amount of hydrofluoric acid added is 0.12 mL, the reaction temperature in step 3 is 210° C., and the reaction time is 1 h.
[0043] Embodiment six:
[0044] The difference from Example 2 is that the reaction temperature in step 3 is 210° C. and the reaction time is 1 h.
[0045] Embodiment seven:
[0046] The difference from Example 2 is that in step 1, the amount of hydrofluoric acid added is 0.37 mL, the reaction temperature in step 3 is 210° C., and the reaction time is 1 h.
[0047] Embodiment eight:
[0048] The difference from Example 2 is that the reaction temperature in step 3 is 210° C. and the reaction time is 1.5 h.
[0049] Embodiment nine:
[0050] The difference from Example 2 is that the reaction temperature in step 3 is 240° C. and the reaction time is 1 h.
[0051] The corresponding parameters of Example 2 to Example 9 are as follows:
[0052]
[0053]
[0054] Table 1 Parameter correspondence table of different embodiments
[0055] The XRD measurement method is used to characterize the structure of the solid-state hydrogen storage material MIL-101 obtained in the above embodiment.
[0056] See also Figure 1 This is the XRD diagram of the solid hydrogen storage material MIL-101 obtained in Example 6. It can be seen from the figure that the diffraction peaks of the prepared materials are completely consistent with the standard spectrum, proving that the prepared materials are all MIL-101 materials. It can be seen from the figure that the diffraction peaks of the materials prepared by the CE method are sharp and strong, forming larger crystals; the diffraction peaks of the materials prepared by the MW method are relatively wide, and the crystal particle size is smaller than that prepared by the traditional solvothermal method.
[0057] Physical adsorption is used to characterize the specific surface area and pore size distribution of the prepared material to obtain the pore structure information of the carbon coating layer. The present invention uses the Autosorb-iQ fully automatic multifunctional gas adsorption analyzer for testing. The test conditions are: 10℃·min -1 The temperature was raised from room temperature to 100°C at a heating rate, kept for 10 min, and then raised to 200°C at the same heating rate before degassing for 600 min. After degassing, a full-pore test was performed, in which the Brunauer-Emmett-Teller (BET) method and the NLDFT calculation model were used to analyze the specific surface area and pore size distribution, and the t-plot method (P / P0=0.4-0.6) was used to analyze the micropore specific surface area and pore volume.
[0058] See also Figure 2Table 2 shows the specific surface area, micropore specific surface area, pore volume and pore size of the material. The specific surface area of the material prepared by microwave method is 3536 m 2 ·g -1 The micropore specific surface area is 3291m 2 ·g -1 The specific surface area of the material prepared by the traditional hydrothermal method is 3049m 2 ·g -1 The micropore specific surface area is 2894m 2 ·g -1 The specific surface area and pore volume of the material prepared by microwave method are larger than those prepared by traditional hydrothermal method, while the pore size is slightly smaller than that prepared by traditional hydrothermal method. The micropore specific surface area and pore volume of the material prepared by microwave method are also larger than those prepared by traditional hydrothermal method.
[0059]
[0060] Table 2 Specific surface area, pore volume, pore size and micropore analysis of chromium-based solid hydrogen storage material MIL-101 synthesized by microwave method and traditional hydrothermal method
[0061] The H2 isotherm adsorption curve of the samples in this study was measured using a fully automatic high-temperature and high-pressure gas adsorption instrument. During the test, the mass of the adsorbent was first weighed, and then the adsorbent was vacuum pretreated to remove impurities such as moisture, and finally the treated sample was subjected to adsorption test. The test temperature was 77K and the test pressure range was 0-50bar.
[0062] The adsorption device uses the static capacity method to calculate the hydrogen storage capacity of the sample. The weight ratio hydrogen storage capacity refers to the weight ratio of the amount of hydrogen that can be stored to the hydrogen storage material, expressed in wt%. During the test, the gas is gradually introduced into the system. The adsorption of gas by the adsorbent will cause the pressure of the system to drop. The gas state equation is used to calculate the gas adsorption amount. By increasing the amount of adsorbate gas in the system to change the pressure and repeating the above operation, the hydrogen isotherm adsorption curve and its equilibrium adsorption amount of the adsorbent under 77K and 0-50bar conditions can be determined and calculated.
[0063] The adsorption amount measured by the instrument is excess adsorption, which needs to be corrected to obtain absolute adsorption. Excess adsorption means that under the same conditions, the amount of H2 absorbed in the free volume equivalent to the total pore volume of the sample exceeds the amount contained. Therefore, this amount is close to the amount of H2 adsorbed on the inner surface of the material. Since the efficiency of filling and compressing gas molecules within the pore range of microporous solids is lower than the efficiency achieved in the free volume, the excess adsorption will reach a maximum value at a certain pressure (usually 20 to 40 bar) and then decrease. Despite the reduction, the measured value at a pressure exceeding the maximum excess adsorption pressure is valuable for evaluating the compressibility of H2 in the material and evaluating the total absorption. The total absorption, also called absolute absorption, corresponds to the amount of hydrogen contained in the boundary formed on the surface of the solid hydrogen storage material MIL-101 crystal. Therefore, this amount includes H2 adsorbed on the surface and H2 compressed within the framework.
[0064]
[0065] Among them, V ex ——Excess adsorption capacity, cm 3 ·g -1 ; V abs ——Absolute adsorption capacity, cm 3 ·g -1 ρ g ——Gas phase density, g·cm -3 ρ a ——density of adsorbed phase, g·cm -3
[0066] The adsorption phase density was calculated using the Langmuir ternary model fitting method, and the fitting relationship is:
[0067]
[0068] Among them, n ex ——excess adsorption capacity, mmol / g; P——adsorption test pressure, MPa
[0069] The gas density at different pressures at 77K was queried by NIST, and ρ was obtained based on linear fitting. g —P, that is, the formula Substitute the relationship into the above formula to get n ex —P. With excess adsorption n ex The experimental pressure P is the dependent variable and the independent variable. The Origin software is used for nonlinear curve fitting to directly obtain the adsorption phase density ρa and the adsorption constants a, b, and m under the pressure calculated by the model. The a value in the fitting value is in mmol / g.
[0070] ρ g =0.0033P-5×10 -6
[0071] See also Figure 3 This is the H2 adsorption-desorption isotherm of the solid hydrogen storage material MIL-101 obtained in Example 6 at 77K and 0-50bar. As can be seen from the figure, the hydrogen adsorption capacity of the material prepared by the microwave method is 5.789wt%, and the hydrogen adsorption capacity of the material prepared by the traditional hydrothermal method is 4.365wt%. The hydrogen storage performance of the material prepared by the microwave method is higher than that of the material prepared by the traditional hydrothermal method. This is mainly attributed to the fact that the micropore specific surface area of the material prepared by the microwave method is larger, and the micropore volume is also relatively large. The storage of hydrogen is mainly affected by the number of micropores, and micropores are more conducive to the adsorption of hydrogen.
[0072] Embodiment 10
[0073] Application of a solid hydrogen storage material MIL-101 in the field of hydrogen storage.
[0074] The present invention uses chromium nitrate nonahydrate Cr(NO3)2·9H2O as the metal center, terephthalic acid H2BDC as the organic ligand, and deionized water as the solvent, and utilizes the microwave method to synthesize the solid hydrogen storage material MIL-101. The reaction time is short and the synthesis process is simple. The sample obtained in the experiment is synthesized by the traditional hydrothermal method. The results show that under the same conditions, the micropore specific surface area of the solid hydrogen storage material MIL-101 synthesized by the microwave method is significantly higher than the micropore specific surface area of the solid hydrogen storage material MIL-101 synthesized by the traditional hydrothermal method. More importantly, the hydrogen adsorption capacity of the solid hydrogen storage material MIL-101 synthesized by the microwave method is also much larger. This shows that the use of the microwave method can increase the micropore specific surface area of the solid hydrogen storage material MIL-101, thereby increasing the hydrogen storage capacity of the material. The present invention uses the microwave method to increase the micropore specific surface area of the solid hydrogen storage material MIL-101 to achieve the benefit of strengthening the hydrogen storage environment. It helps to reduce greenhouse gas emissions, promote the use of renewable energy, improve air quality, and promote the sustainable development of society.
[0075] The above is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention shall be implemented according to the conventional means in the art unless otherwise specified and limited.
Claims
1. A solid hydrogen storage material, characterized in that: The solid-state hydrogen storage material MIL-101 has a multi-level pore structure and a specific surface area of 3049 m 2 ·g -1 The micropore volume is 1.42-1.70cm 3 ·g -1 , at a temperature of 77K and a pressure of 50 bar, the solid-state hydrogen storage material MIL-101≥4.365wt%.
2. A method for preparing a solid hydrogen storage material, characterized in that: The solid-state hydrogen storage material is the solid-state hydrogen storage material described in claim 1, and the preparation method comprises the following steps: Step 1: weigh 20-30 parts by mass of chromium nitrate nonahydrate and 8-12 parts by mass of terephthalic acid using an electronic balance, place them in a container, add 25-35 parts by mass of deionized water and 2-3 parts by mass of hydrofluoric acid to obtain a mixed solution A; Step 2: After ultrasonically mixing solution A for 30 minutes, transfer it to a microwave reactor lined with polytetrafluoroethylene, seal the microwave reactor and place it in a microwave hydrothermal reactor for reaction; Step 3: Set the microwave power to 600 W, the temperature to 200-240 ° C, and the reaction time to 0.5-1.5 h; Step 4: After the reaction is completed, the mixture is naturally cooled to room temperature, the reaction product is poured into a centrifuge tube and placed in a centrifuge, and the crude product is collected by centrifugation at a speed of 4000 r / min; Step 5: Add 20-30 parts by mass of N,N-dimethylformamide DMF to the crude product, put it into a magnetic heating stirrer for activation, set the temperature to 70°C, the speed to 500r / min, and the activation time to 3h; Step 6: After activation, the reaction product is placed in a centrifuge and centrifuged at 4000 r / min to collect the crude product; Step 7: Add 15-25 parts by mass of anhydrous ethanol to the crude product, place it in a magnetic heating stirrer for activation, set the temperature to 60°C, the speed to 500r / min, and the activation time to 3h; Step 8: After activation, the reaction product is placed in a centrifuge and centrifuged at 4000 r / min to collect the product; the product is then transferred to a beaker, placed in an oven, and dried at 80°C for 12 hours to obtain a dry solid-state hydrogen storage material MIL-101 sample.
3. The method for preparing a solid hydrogen storage material according to claim 2, characterized in that: In the step 2, the synthesis instrument is a microwave reactor.
4. The method for preparing a solid hydrogen storage material according to claim 2, characterized in that: In step 3, the power of the microwave heating is 600 W, the temperature of the microwave heating is 200-240° C., and the time of the microwave heating is 0.5-1.5 h.
5. Application of the solid-state hydrogen storage material MIL-101 according to any one of claims 1 to 4 in the field of hydrogen storage.